efektivitas Penggunaan Metode Suggestopedia terhadap Kemampuan Menulis Siswa Sekolah Dasar - Ulfayani Hakim; Syamsuriyanti Syamsuriyanti; Mutiara Mutiara (Jurnal Ilmu Pendidikan Dasar Indonesia, 2023)
This type of research is experimental research. The research variables are the independent variable in the form of suggestopedia method and the dependent variable, namely students' writing ability. The population of this study were students of grades VA and VB. The sampling technique was simple random sampling and class VB as the experimental group and class VA as the control group. The data collection technique was a test technique. The reliability test was carried out using the Cronbach alpha coefficient formula with an alpha of 0.732. Content validity with expert judgment. The normality test results showed that the research data were normally distributed. The homogeneity test results show that the variance of the research data is homogeneous. The results showed that there was a significant difference in students' writing skills between students who learned to write free essays using the suggestopedia method and students who learned to write free essays without using the suggestopedia method. This is shown from the calculation of t test obtained df62, p = 0.040 <0.05. Learning to write free essays is more effective using the suggestopedia method than learning to write free essays without using the suggestopedia method. This is indicated by the mean value of the experimental pretest of 19.78, and the mean value of the experimental posttest of 22.28, which means there is an increase of 2.5. The mean score of the control pretest was 18.91 and the mean score of the control posttest was 20.91, which means there was an increase of 2. The difference in the increase in the average score of the two groups was 0.50.